2017
DOI: 10.1039/c7cc02078c
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed intermolecular [3+3] cycloaddition of vinyl aziridines with C,N-cyclic azomethine imines: stereospecific synthesis of chiral fused tricyclic 1,2,4-hexahydrotriazines

Abstract: An atom-economic route to ring-fused 1,2,4-hexahydrotriazines relying upon a new synthetic application of vinylaziridines in a rhodium-catalyzed intermolecular [3+3] cycloaddition of C,N-cyclic azomethine imines has been reported. Highly efficient chirality transfer in the present transformation was also observed, providing a new method for the synthesis of sp-carbon-rich 1,2,4-hexahydrotriazines in an enantioselective manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…In 2014, Liu, Yang, and co-workers developed a one-pot Cu­(II)-catalyzed coupling–cyclization process which provided an efficient route to pyrrolo­[2,1- f ]­[1,2,4]­triazine-fused isoquinolines in average good yields (Scheme , eq 1) . Recently, Feng and Zhang et al reported a rhodium-catalyzed intermolecular [3 + 3]-cycloaddition of vinylaziridines with C , N -cyclic azomethine imines for the synthesis of isoquinoline-fused triazines with excellent diastereoselectivities (Scheme , eq 2) . Despite those elegant contributions, further development of efficient methodologies for the synthesis of biologically important isoquinoline-fused triazines from readily available precursors is still appealing and highly desirable.…”
mentioning
confidence: 99%
“…In 2014, Liu, Yang, and co-workers developed a one-pot Cu­(II)-catalyzed coupling–cyclization process which provided an efficient route to pyrrolo­[2,1- f ]­[1,2,4]­triazine-fused isoquinolines in average good yields (Scheme , eq 1) . Recently, Feng and Zhang et al reported a rhodium-catalyzed intermolecular [3 + 3]-cycloaddition of vinylaziridines with C , N -cyclic azomethine imines for the synthesis of isoquinoline-fused triazines with excellent diastereoselectivities (Scheme , eq 2) . Despite those elegant contributions, further development of efficient methodologies for the synthesis of biologically important isoquinoline-fused triazines from readily available precursors is still appealing and highly desirable.…”
mentioning
confidence: 99%
“…Thus, great research interests have been devoted to their facile synthesis in the past several years. However, to the best of our knowledge, only very limited methods have been developed for the construction of isoquinoline‐fused triazine derivatives, which are all based on the transition‐metal catalyzed cyclization or cycloaddition process, including rhodium, copper, and silver . Therefore, further development of highly efficient strategies for the preparation of these important fused heterocyclic ring structures under transition‐metal free conditions is of great significance.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis of 1,2,4-hexahydrotriazine derivative (36) was developed by Chao-Ze Zhu et alvia [Rh(NBD) 2 ]BF 4 catalyzed [3 + 3] cycloaddition reaction of (R)-vinyl aziridines (34) with Nimino isoquinolium ylide (35) (Scheme 12). [23] The product was formed through consecutive (б + п) rhodium species subse- [3 + 3]-cycloaddition reaction of α-acidic isocyanide with azomethine imine in presence of Cu catalyst. [21] Scheme 11.…”
Section: Metal Catalyzed Approachmentioning
confidence: 99%